Effect of carbamide peroxide on the push-out bond strength of different composition glass-ionomer cement to root canal dentin when used as cervical barrier - Lima, Suellen Nogueira Linares; Venção, Ana Carolina [UNESP]; Kuga, Milton Carlos [UNESP]; Magro, Miriam Graziele [UNESP]; Guiotti, Aimeé Maria [UNESP]; Segalla, José Claudio Martins [UNESP]; Jordão-Basso, Keren Crisitina Fagundes [UNESP]; Ricci, Weber Adad [UNESP]; Tonetto, Mateus Rodrigues; Bandéca, Matheus Coelho (Jaypee Brothers Medical Publishing, 2015)
Aim: To evaluate the effect of 37% carbamide peroxide on the bond strength of conventional or resin-modified glass-ionomer cements when used as a cervical barrier in endodonticallytreated teeth. Materials and methods: After root canal instrumentation and obturation, 40 specimens of the cement-enamel junction were obtained after transversal root canal sectioning from human extracted canines. The root canal specimens were standardized and filled with the following materials (n = 10, each group): G1: zinc phosphate (control), G2: Ketac glass-ionomer, G3: vitrebond glass-ionomer or G4: GC GL glass-ionomer. After 24 hours, the specimens were subjected to an application of 37% carbamide peroxide for 21 days, changed each 7 days and stored in an artificial pulp chamber. The specimens were then submitted to push-out bond strength testing with an electromechanical test machine (EMIC) and the failure mode in each specimen was analyzed with confocal microscopy (LEXT). Results: G3 and G4 showed higher bond strengths values than the other groups (p < 0.05), and were similar to each other (p > 0.05). G1 showed the lowest bond strength value (p < 0.05). Conclusion: Glass-ionomer cements showed higher bond strength values than the zinc phosphate cement, and resinmodified glass-ionomer cements presented the highest push-out values to root canal dentin (GC, GL and Vitrebond).
Keywords: Bleaching agents; Carbamide peroxide; Dentinbonding agents; Endodontic; Glass ionomer cements